OTITIS MEDIA: A PROSPECTIVE STUDY IN CENTRAL INDIA - DR. TEKLAL PATEL,; DR. HARI SHANKAR SHARMA, (International Journal of Pharma and Bio Sciences, 2014)
otitis media are challenging disease in developing countries like India. Rural population is more commonly affected. The microbiology of otitis media is different in various regions that affect the use of proper antibiotics. This study was conducted on 128 patients of otitis media irrespective of age and sex. A complete physical and otological examination was performed. A questionnaire was prepared. A swab was prepared from ear discharge, if any, and sends for microbiological examination. Male female ratio was found to be 1.33: 1. Maximum numbers of cases were reported between 1-10 yrs. Commonest symptom was otalgia and otorrhea together. 5.88% cases showed both bacteria and fungi, 15.29 were negative for both bacteria and fungi. Pseudomonas aeruginosa was the commonly found bacteria and Candida albicans was the commonly occurring fungus.